Causal relationship between Crypto currencies: An Analytical Study between Bitcoin and Binance Coin - MALLICK, SANTOSHA KUMAR (The journal of contemporary issues in business and government, 2020)
The author in this article studies the price volatility of Binance Coin to its volume and Bitcoin price and analyzes the theoretical and useful relationship between Bitcoin and Binance Coin cryptocurrencies. The current increase on the importance of cryptocurrencies is examined by generalizing the available literature on the essential characteristics and association of Bitcoin and Binance coin prices. On the basis of the problems and existing research on cryptocurrencies the relationship between Binance coin and Bitcoin prices is analysed. A statistical model of the cryptocurrency relationship analysis is offered, which may be useful to establish that the relationship among cryptocurrencies. The main findings is that that a relationship exists between the prices of Bitcoin and Binance coin, and this relationship can be applied for diversification of portfolio and risks when trading on the cryptocurrency exchange. The rationale of this study is to construct an instrument which can explain the relationship between the price of Binance coin and its volume and the price of Bitcoin and to forecast their changes over a period of time. This article analyzes the price volatility of Binance coin as dependent on the price of Bitcoin.